Pengaruh Nilai-Nilai Pencak Silat terhadap Kepribadian Siswa Madrasah - Aziz, Abdul; Suharmoko, Suharmoko (Tarbiyah STAIN Sorong, 2019)
This research will investigate how much influence the values of Pencak silat on the personality of students in MTs Muhammadiyah 1 Salawati, Sorong Regency. The purpose of this study is to describe the influence of Pencak silat values on student personality. The study population was all students who participated in martial arts activities. This research uses quantitative research. Data collection methods are carried out through observation, documentation, and questionnaires. This research was conducted during extracurricular activities. Data collection techniques are done using a questionnaire (Questionnaire). The collected data were analyzed using descriptive statistical analysis with the help of SPSS 16 statistical data processing software. The results of the data analysis showed that there was no significant effect between Pencak silat values on the personality of students of MTs Muhammadiyah 1 Salawati, Sorong Regency, which only had an effect of 11, 5%.